To be or not to be assertive, that is the question: Ser o no ser asertivo, esa es la cuestión (Papeles, 2023)
Introduction: This paper analyzes assertive communication (comunicación asertiva). Its main goal is showing tensions inherent to the demand “Be assertive!”. For this, it presents what limits and boosts this way of communication. Teacher’s communication is immersed in pressures being objective, affective or persuasive? Some possibilities are clarified to face them. Methodology: The plausible results of 37 studies about comunicación asertiva were reviewed and synthesized; while simultaneously, exposing limits not considered. They are illustrated by doing a meta-analysis of comunicación asertiva based on pedagogic, sociologic, psychologic, political and complex theories. Results and discussion: The offers of these 37 texts were stressed with contradictions: i) pedagogical/performative versus scientific/objective, ii) political: obey versus command, and iii) social versus individual versus circumstantial. A finding highlights the need to assess what type of communication to put into play. Conclusions: It invites to complement educational communication, considering what is valuable in comunicación asertiva and presenting limits that guide towards enhancing it when playing and socializing, or well, by pointing towards a better world. It suggests ways of communicating that improve human life by admitting strain to be assertive or not to be assertive?
Keywords: Communication; education; game; socialization